Application Of Fundamentals In Optimizing Platinum Concentrator Performance ? Synopsis - M. M. Valenta (The Southern African Institute of Mining and Metallurgy, 2011)
A number of challenges face platinum concentrator plant operators. These challenges include the increase in operating costs, the increase in smelter cost for the processing of concentrate, the shortage and cost of power, and the tightening of specifications on concentrate quality by the toll-smelting operations. Over the years the focus has moved from extracting the platinum group metals (PGM) from the Merensky Reef to the UG2 reef. This has a number of advantages, including the higher ?basket price? for UG2 concentrate, reduced mining cost per unit volume as a result of the higher density of UG2, and the reduction in overall concentrate tonnage to be smelted. In many cases the Merensky ore has been fully exploited and it makes sense for the focus to shift to the UG2 ore that can be accessed through the Merensky shaft infrastructure. The presence of relatively high levels of chromite in UG2 concentrate is, however, a major disadvantage due to the problems associated with smelting such a concentrate in conventional submerged arc furnaces. In addition to increasing the specification on the minimum PGM grade of concentrates, smelters have had to impose strict specifications on the levels of chromite in the concentrate. The threat of high penalties has forced concentrators to change their modus operandi, often resulting in a significant loss in recovery. The final concentrate grades and PGM recoveries are shown to vary significantly throughout the industry. The reasons for this include varying ore mineralogy and different operating philosophies. This would therefore imply that the opportunity exists to optimize the operations by considering fundamental aspects such as the PGM mineralogy and the application of appropriate technologies. By returning to the fundamentals of flotation and applying the findings of detailed process reviews, it has been possible to increase the concentrate PGM grade, reduce the concentrate chromite grade, and in some cases increase the recovery of PGM to concentrate. This paper presents case studies where this approach has been used to successfully optimize concentrator performance, resulting in lower operating cost and higher PGM production. Keywords Process optimization, platinum concentrator, milling, flotation, grade, recovery